Duch Paraklet a pamięć Kościoła w ujęciu czwartej Ewangelii - Kluska, Branislav (Verbum Vitae, 2020)
Jesus in his farewell speech announces the sending of the Paraclete (Jn 14:26), whose task will be to remind Jesus’ disciples of what Christ had taught them. The article tries to answer the question: What is a proper understanding of the Spirit-Paraclete’s action upon disciples’ memory? The author of the article addresses this issue from the perspective of biblical theology. First, he presents in a synthetic way the understanding of memory in the Bible and the basic assumptions of the theory of social memory. Then he analyzes the text and offers a theological interpretation of the promise of Jn 14:26 and other texts of the Fourth Gospel where a motif of remembrance is present (2,17.22; 12,16). Memory is an essential element of the experience of the post-paschal Church. The activity of the Spirit connects the present of the Church with the past of the historical Jesus. The memory animated by the Paraclete and enlightened by the experience of the Resurrection always focuses on the words of the Scriptures and the words of Jesus. The believers’ social memory within Johannine Christianity is not sufficient in and of itself, but needs the Holy Spirit’s action in order to effectively build the community’s identity.